Determination of parasites in faeces in red-eared slider turtle (Trachemys scripta elegans) in captivity from the Maule Region, Chile - Villalobos, Felipe (2020)
The study aimed to detect the presence of endoparasites in faecal samples of Trachemys. scripta elegans from private households in the Maule Region, Chile. The sampling was conducted to determine the prevalence of gastrointestinal parasites in 35 individuals (22 females and 13 males), using the Teuscher coproparasitic technique. Only one sample of a female turtle was positive (2.85%), corresponding to an undetermined species of coccidia.